Digital Transformation: Meeting the Challenges: conference proceedings / 31st Bled eConference, June 17 - 20, 2018, Bled, Slovenia (University of Maribor Press, 2018)
Bled eConference, organized by University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interactions since 1988. Bled eConference is the oldest, most traditional and well renowned conference in the field with more than 30 years of tradition. The theme of this year’s conference is dedicated to “Digital Transformation – Meeting the Challenges”. The evolution of digital technologies and solutions has significantly impacted the way in which business is conducted and have big implications on our lives. Nowadays digital economy calls for transformation of businesses, governments, education and societies as whole. It also calls for enabling policies and politics for cross border and global digital business. In this year’s conference, we address various aspects of digital transformation and provide directions and guidelines for organizations to meet and overcome these challenges on their way towards successful digital transformation. Themes covered in the papers of these proceedings are focused on: digital transformation; business model innovation; blockchain and social media; big data, data science, and decision support systems; e-health, digital wellness and wellbeing; new applications and organizational models; and novel approaches and cases in education in digital economy.